When They Came for You : Elegies of resistance. - Barnett, Christopher (Wakefield Press, 2016)
In this solemn act of remembering, the poet pulls onto his shoulders the weight of ""this world gone wrong"". In the tradition of Mayakovsky and Hikmet to read publicly ""to confront people more than to console them"", this is a social poem to ""like"" and ""share"". In a culture that longs for closure, this will leave all your doors hanging open.